Implementation of Integrated Farming with the Nuance of Good Agriculture Practice Based on the AgroMap Info Web Towards Achieving SDGs 2030 in Balesari Village - Premastin, Olivia Listyaning; Hidayah, I'anatul; Aradea, Bagus; Herawati, Rani; Ardianto, Muhammad Irvan (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The aim of community service is to empower the community and educate the community regarding organic farming through making liquid organic fertilizer, integrated farming through an aquaponic system, and applying the AgroMap Info website for agricultural sustainability.Method: The program was conducted offline using the Participatory Rural Appraisal (PRA) method, involving the community as active participants. Activities were held in various hamlets to ensure full engagement and practical learning.Practical Applications: The program provided practical knowledge on organic farming and aquaponics, promoting better agricultural practices. The AgroMap Info website helped farmers access critical agricultural data, enhancing sustainability.Conclusion: Provide a concise summary of the primary findings derived from the study. Emphasize the importance of the results and their contribution to a broader comprehension of the topic or resolution of the research issue outlined in the introductory section.